Adaptation and Validation of the Autism Mental Status Examination (Amse) in Chile: Seeking to Reduce the Diagnostic Gap; [Adaptación y Validación del Examen de Estado Mental del Autismo (Amse) en Chile: Buscando Reducir la Brecha Diagnóstica] - Yañez-Medina, C (Sociedad Chilena de Pediatria, 2023)
Early detection of Autism is a challenge in Chile and Latin America. Gold-standard evaluations are expensive and difficult to access. The Autism Mental Status Exam (AMSE) is a brief, structured, observational instrument for clinical use with promising results. Objective: To adapt and validate the AMSE in a sample of Spanish-speaking children and adolescents at risk of Autism Spectrum Disorder (ASD) using the ADOS-2 as a comparison. Subjects and Method: Children and adolescents aged 15m-17yo consulting due to language and communication problems and/or suspected ASD. The AMSE was administered during clinical evaluation. The ADOS-2 was administered by independent evaluators, blinded to the study, which determined diagnostic categories as: Non-Autism Spectrum Disorder (Non-ASD), Autism Spectrum Disorder (ASD), or Autism (AUT). Psychometric characteristics of the AMSE were assessed and, using the ROC curve, a cut-off point was calculated, identifying sensitivity, specificity, positive, and negative predictive value. Results: Sixty-four children participated, 56 were males (87.5%), with a mean age of 6.6y (SD: 3.6). They were distributed as Non-ASD: 12 (18.8%), ASD: 19 (29.7%), and AUT: 33 (51.6%) according to the ADOS-2. The AMSE scores differed significantly among the three categories (p<0.0001). Internal consistency was moderate and Cronbach’s alpha was 0.61. The cut-off point was ≥6 (Sensitivity 0.79, Specificity 0.92, AUC: 0.91). A second analysis according to language level suggests a greater diagnostic accuracy of the AMSE for the group with lower language development, maintaining the same optimal cut-off point (≥6). Conclusions: The AMSE shows adequate psychometric properties, good capacity, and accuracy to support the diagnosis of ASD. Its brevity, low cost, and easy integration into clinical practice make it an alternative with great potential for timely recognition and referral of children with ASD. © 2023, Sociedad Chilena de Pediatria. All rights reserved.
Keywords: Autism; Autism Spectrum Disorder; AMSE; ADOS-2; Early Detection; Screening